Sistem Pendukung Keputusan Dalam Pemilihan Personil Polisi Direktorat Reserse Narkoba Berprestasi Menggunakan Metode ELECTRE - Dafirius Lombu (Journal of Computer System and Informatics (JoSYC), 2020)
The Narcotics Investigation Unit (Sat Res Narcotics) is part of the National Police of the Republic of Indonesia (Polri) tasked with conducting or fostering the function of investigating and investigating narcotic crimes including counseling and coaching in the framework of prevention, misuse, overcoming and rehabilitation of narcotics abuse victims. The Directorate of Narcotics Investigation at Medan Police Department has police personnel serving in the drug detective unit. Of course, each personnel has different abilities, for example being able to complete the tasks given by superiors who later said the personnel were achievers and so forth. The selection of outstanding police personnel in the Directorate of Drug Investigation is still manualised without the role of a computerized system. There are often errors in the selection of outstanding police officers in the Directorate of Drug Detachment, namely the miscalculation of criteria that may lead to misunderstanding of personnel and the presence of subjective elements of dislike or dislike. based on criteria that have been determined in the selection of police officers directorate of outstanding drug investigators. Therefore, to facilitate the selection, it can use the computerized Electre method to get better results. The Elect (Elimination Et Choix Traduisant La Realite) method is one of the methods in Multi Criteria Decision Making (MCDM) which is based on the concept of outranking by using a pairwise comparison of alternatives for each suitable criterion. Although it does not guarantee its efficiency, using this method can help decision makers make decisions more accurately in the selection of high-achieving police directorate police officers.